2020
DOI: 10.3390/ijms21114109
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulatory Role of the TRPA1 Receptor in Acute and Chronic Airway Inflammation Mouse Models

Abstract: The Transient Receptor Potential Ankyrin 1 (TRPA1) cation channel expressed on capsaicin-sensitive afferents, immune and endothelial cells is activated by inflammatory mediators and exogenous irritants, e.g., endotoxins, nicotine, crotonaldehyde and acrolein. We investigated its involvement in acute and chronic pulmonary inflammation using Trpa1 gene-deleted (Trpa1−/−) mice. Acute pneumonitis was evoked by intranasal Escherichia coli endotoxin (lipopolysaccharide: LPS) administration, chronic bronchitis by dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…TRPA1 and TRPV1 are expressed and often co-localized on the capsaicin-sensitive peptidergic afferents densely innervating the lung [41], as well as on pulmonary epithelial cells lymphocytes and bronchial smooth muscle cells [42,43]. TRPA1 and TRPV1 have been reported to be protective against the LPS-induced acute lung injury model [44][45][46]. The potential interactions of these essential oil components with the TRP ion channels in the LPS-induced acute lung injury model might open future drug developmental perspectives worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 and TRPV1 are expressed and often co-localized on the capsaicin-sensitive peptidergic afferents densely innervating the lung [41], as well as on pulmonary epithelial cells lymphocytes and bronchial smooth muscle cells [42,43]. TRPA1 and TRPV1 have been reported to be protective against the LPS-induced acute lung injury model [44][45][46]. The potential interactions of these essential oil components with the TRP ion channels in the LPS-induced acute lung injury model might open future drug developmental perspectives worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings regarding the role of TRPA1 in LPS-induced inflammation have been equivocal. By comparing the responses between wild-type and trpa1 –/– mice, Hajna et al (2020) demonstrated that TRPA1 protects against LPS-induced acute pneumonitis and hyperresponsiveness. Kamei et al (2018) , however, reported that TRPA1 plays no role, because TRPA1 knockout does not alter LPS-induced bladder inflammation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the functional importance of TRPA1 in LPS-induced consequences have reported equivocal findings. TRPA1 protects against LPS-induced pneumonitis ( Hajna et al, 2020 ) and does not contribute to LPS-induced bladder inflammation ( Kamei et al, 2018 ) in mice. However, TRPA1 mediates LPS-induced lung inflammation in mice ( Liu et al, 2020 ) or inflammatory responses to LPS in vitro ( Prandini et al, 2016 ; Yin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…LPS molecules on the surface of bacterial particles increase activity of TRPV4 in a matrix stiffness-dependent manner [ 57 ]. Of note, multiple TRP channels, including TRPV1 [ 58 , 59 , 60 ], TRPV4 [ 23 , 61 ], TRPA1 [ 60 , 62 , 63 , 64 , 65 ], TRPM3 [ 60 ] and TRPM8 [ 60 ] have been described as targets of LPS, probably via the induction of modifications in the plasma membrane [ 66 , 67 ]. Therefore, these TRP channels may mediate the action of PM contaminated with this bacterial component.…”
Section: Effects Of Pm On Trp Channelsmentioning
confidence: 99%
“…These components can activate TRP channels and cause deleterious effects associated with cancers, heart attack, vascular abnormalities and other pathological processes. TRPA1 is a remarkable airway chemical sensor with roles in both protective reflexes (sneezing, coughing) and pathophysiological responses (inflammation, bronchial hyperreactivity) [ 40 , 58 ]. The components found in CS can activate TRPA1 channels in the plasma membrane of cells located along the respiratory tract.…”
Section: Effects Of Pm On Trp Channelsmentioning
confidence: 99%